A Derivative and Inversion-Free Quasi-Newton Power Flow for a Droop-Regulated Islanded AC Microgrid - Singh A.; Maulik A. (My University, 2025)
The autonomous power-sharing among dispatchable sources in an islanded microgrid occurs due to a droop-control philosophy at the local control level. The operating principle of a droop-regulated islanded microgrid differs from that of a grid-connected microgrid or a traditional power system. Hence, power flow analysis approaches proposed and used extensively for the steady-state analysis cannot accurately depict the steady-state picture of a droop-regulated islanded microgrid. In this paper, a power flow technique for a droop-regulated islanded microgrid is proposed. The proposed algorithm does not need the calculation of the Jacobian elements. Also, a matrix inversion operation is not required. A quasi-Newton “Broyden’s” approach with a backtracking feature is adopted to estimate an approximation of the inverse of the Jacobian. The proposed technique has a low computation burden. The validation of the proposed algorithm is provided by simulation studies on two different test systems with EMTDC/PSCAD simulation results, and comparisons with some reported algorithms show that the proposed technique has at least ∼ 72.9 % lower computational time. © 2022, The Author(s), under exclusive licence to Shiraz University.